IMPACT OF GOOD GOVERNANCE ON PUBLIC DEBT IN NIGERIA - AYENI , ABIGAEL. F; NJOKU , MITCHELL. O. B (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Nigeria has faced substantial public debt challenges, exacerbated by corruption and inadequate accountability. This study looks at how good governance has an effect on Nigeria's public debt from 2003 to 2022. It utilizes data on corruption control, political stability without violence, rule of law, and voice and accountability from the World Bank Development Indicator (2023).Details about total external debt and information and communication technology come from the Central Bank of Nigeria Statistical Bulletin (2023). The autoregressive distributed lag model shows in its long-term analysis that PSAV, RLE, VAE (lag-1), and ICT have a positive effect on public debt, while CCE and VAE have a negative effect on public debt. Short-term results show that PSAV RLE, and ICT keep having a positive effect on public debt, while CCE and VAE keep having a negative effect. The study concludes that effective governance, marked by increased accountability and reduced corruption, can significantly alleviate public debt issues. It recommends that the Nigerian government implement robust anti-corruption policies, strengthen the rule of law, and enhance transparency in debt management. Additionally, it suggests improving legislative oversight to ensure all borrowing decisions are scrutinized and approved by parliamentary bodies, with appropriate tools and training for legislators. These measures are essential for better public debt management and for building stakeholder trust